2022
DOI: 10.3389/fpls.2022.935090
|View full text |Cite
|
Sign up to set email alerts
|

Foliar spray of silica improved water stress tolerance in rice (Oryza sativa L.) cultivars

Abstract: Rice (Oryza sativa L.) is a major cereal crop and a staple food across the world, mainly in developing countries. Drought is one of the most important limiting factors for rice production, which negatively affects food security worldwide. Silica enhances antioxidant activity and reduces oxidative damage in plants. The current study evaluated the efficiency of foliar spray of silica in alleviating water stress of three rice cultivars (Giza178, Sakha102, and Sakha107). The seedlings of the three cultivars were f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…This is due to water limitations under stress conditions so that during growth, the results of their metabolism are more focused on roots to survive drought stress [18]. The research results by Pipai [19] treatments without stress and drought stress gave significant and significantly different results on the weight of plant parts, including grain. Grain weight without stress has a higher weight than stress because the supply of photosynthesis needs is not disturbed in normal water conditions, while under stress conditions, the formation of assimilated substances to fill the grain is inhibited.…”
Section: A Plant Height Dry Weight Plants and Dry Weight Rootsmentioning
confidence: 99%
“…This is due to water limitations under stress conditions so that during growth, the results of their metabolism are more focused on roots to survive drought stress [18]. The research results by Pipai [19] treatments without stress and drought stress gave significant and significantly different results on the weight of plant parts, including grain. Grain weight without stress has a higher weight than stress because the supply of photosynthesis needs is not disturbed in normal water conditions, while under stress conditions, the formation of assimilated substances to fill the grain is inhibited.…”
Section: A Plant Height Dry Weight Plants and Dry Weight Rootsmentioning
confidence: 99%
“…Drought is one of the most catastrophic climate catastrophes that endangers global agricultural productivity [15]. Water deprivation prevents cell development, which leads to short stems, shorter internodal lengths, weakened root systems, and reduced tillering capacity [27].…”
Section: Introductionmentioning
confidence: 99%
“…Different cereal crops have different adaptive reactions to deal with drought [33] To counteract the negative impacts of drought stress, plants exhibit a variety of morphological, physiological, biochemical, and molecular characteristics [12]. Some of the physiological systems involved in a plant's reaction to drought stress conditions include cell and tissue water preservation, cell membrane stability, and endogenously produced growth regulators [15]. Plants modify gene expression at the molecular level to counteract the potentially harmful consequences of decreased water supply.…”
Section: Introductionmentioning
confidence: 99%
“…(2016) showed that organic soil amendments stimulate antagonistic activities of microorganisms to soil-borne diseases and decomposition of organic matter in the soil, which resulted in bioactive antifungal or nematicidal compounds accumulation in the soil. Soils treated with a high level of organic matter reduced the Fusarium rot root index, and improved yields occurred ( Naseri, 2014 ; El-Saadony et al, 2021a ; Abd El-Aty et al, 2022b ; El-Ashry et al, 2022 ; El-Marzoky et al, 2022 ; El-Okkiah et al, 2022a ).…”
Section: Introductionmentioning
confidence: 99%